The interior spreading story of Labrador Sea Water - Chomiak, Leah; Volkov, Denis; Schmid, Claudia (Frontiers in Marine Science, 2023)
The unique convective anomalies of Labrador Sea Water (LSW) can be used as advective tracers when assessing equatorward spreading pathways and timescales of LSW. In this study, we explore advective pathways of two LSW classes formed in the 1990s and early 2000s, respectively, along constant neutral density planes. Hydrographic observations showcase the prevalence of both LSW classes within the Atlantic interior, supporting a recirculation feature that branches from the Deep Western Boundary Current (DWBC) at 36°N among other pathways. Spreading characteristics of both LSW classes from the Labrador Sea to the subtropics are reinforced through a spatial pattern analysis of salinity anomalies and geostrophic velocities along the characteristic neutral density planes of each respective LSW class. We observe both classes to advect out of the Labrador Sea to (i) the eastern subpolar region and down the eastern boundary towards the Atlantic interior, (ii) directly into the Atlantic interior likely from an injection by recirculations from the subpolar gyre and DWBC leakage, and (iii) equatorward along the western boundary via the DWBC. Findings highlight the abundance of LSW within the Atlantic interior, not just along the western boundary, suggesting that interior pathways play an influential role on the export of these subpolar climate signals.